Presenting the ideal model of academic performance based on psychological capital, personal adaptability and problem-solving skills in female students - Zeinab Soleimani Hooni; Alireza Manzari Tavakoli; Hamdollah Manzaritavakoli; Najmeh Hajipour (مطالعات روانشناسی تربیتی)
The aim of the current research was to design the ideal model of academic performance based on psychological capital, individual adaptation and problem solving skills in female students of Kerman city (academic year 1402-1401). The descriptive research method was of the correlation type and in the form of structural equation modeling. The statistical population of this research included all female students of the second level of secondary school in Kerman city with a number of 3875 people and the sample size was estimated to be 384 people based on Cochran's formula. Considering the possibility of removing and usability of some questionnaires, the number of 400 students was determined After removing incomplete questionnaires, 380 people were selected by two-stage cluster random sampling method. Psychological capital Luthans (2007), problem solving Hepner and Petersen (1982), Individual compatibility California Clark et al.'s (1953), and academic performance Dortaj (2013) questionnaires were used to collect information. According to the appropriate fit of the research variable measurement model, the results showed that all indicators were acceptable. The results obtained from the model test have shown that the direct relationship between the variables of psychological capital, Individual compatibility, problem solving skills and academic performance is positive and significant.